Elevated CO 2 does not alter behavioural lateralization in free‐swimming juvenile European sea bass ( Dicentrarchus labrax ) tested in groups - Dominic M. Jarvis; Edward C. Pope; Mathieu Duteil; Ines Fürtbauer; M. Rowan Brown; Richard J. Davis; Andrew J. King (Journal of Fish Biology, 2022)
The authors investigated left–right turning preferences of n = 260 juvenile European sea bass ( Dicentrarchus labrax ) reared in ambient conditions and ocean acidification (OA) conditions or in ambient conditions but tested in OA water. Groups of 10 individuals were observed alone in a circular tank, and individuals' left and right turning during free‐swimming was quantified using trajectory data from the video. The authors showed that near‐future OA levels do not affect the number of turns made, or behavioural lateralization (turning preference), in juvenile D. labrax tested in groups.